Understanding the effects of off-state and hard-switching stress in gallium nitride-based power transistors. (12th November 2020) - Nicola, Modolo; De Santi, Carlo; Minetto, Andrea; Sayadi, Luca; Sicre, Sebastien; Prechtl, Gerhard; Meneghesso, Gaudenzio; Zanoni, Enrico; Meneghini, Matteo
Abstract: The aim of this paper is to improve the understanding of gallium nitride (GaN) high electron mobility transistors (HEMTs) submitted to hard switching operation, with focus on the hot-electron phenomena. This is becoming a hot-topic both for the scientific community and for the industry. The analysis is carried out through a cross-comparison of three different experimental techniques: conventional Pulsed-IV characterization, a novel pulsed-drain current transient (P-DCT) method, and a custom-developed hard switching test protocol. Hard switching analysis was performed through a novel system able to test the device in hard-switching conditions with an unprecedented turn-on slew-rate of 25 V ns −1 on-wafer level. This allows μ s to investigate the impact of hard switching in terms of (i) locus trajectory, (ii) dissipated power, and (iii) dynamic R on increase. Furthermore, the accumulation of switching stress is assessed by repeating the experiment with increasing frequency, from 1 kHz to 100 kHz. The extensive cross-analysis offers a novel insight on the degradation mechanisms occurring in power GaN HEMTs. The results collected within this paper allow: (1) to evaluate the dynamic behavior under both soft- and hard-switching stress, thus differentiating off-state and semi-on-state stress; (2) to pinpoint hot-electrons as the main cause of the current collapse observed in semi-on; (3) by comparing the results obtained from P-DCT and Hard Switching Analysis we demonstrate that the hot-electron trapping is a very fast process which can happen in few ns. The related trapping and de-trapping kinetics are investigated in detail. The results described within this paper provide novel insight on the important role of hot-electrons in the dynamic R on increase during hard switching operations.